Air Corporate Governance and Suspicion of Corruption in Supply Chain Management: The Case of Tunis Air Airlines - Salem Y. Lakhal; Camelia Lakhal (International Journal of Supply Chain Management, 2023)
The corporate governance of airlines companies is not a well studied area. As corruption is a criminal act, the issue is sensitive, and the doors are not opened for researchers. This article aims to contribute to the scarce literature surrounding this topic in order to overcome the lack of research. By staying studying this topic at a general lever and analyzing most of the supply chain activities of real airline companies, we can detect which activities within the supply chain present the most potential where corruption could take place. Propositions will be developed about the characteristics that need to be built into the value chain activities to be robust against corruption. These analyses and propositions are grounded in a case study of the Tunisian airline, Tunis Air. Although this company is not among the biggest airlines in the world, it’s governance could be a structural example in this area of study.